Factors influencing the adoption of halal cosmetics among young generation in Melaka / Fatin Aqilah Salim - Salim, Fatin Aqilah (Faculty of Business and Management, 2018)
Topic for this study is factors influencing the adoption of Halal cosmetics among young generation in Melaka. The research is based on sample of 100 respondents and the objective is to determine how product characteristics, social influence, and consumer innovativeness influencing the adoption of Halal cosmetics. As the results show that product characteristics, social influence, and consumer innovativeness have impact on the adoption of Halal cosmetics. Based on three variables, product characteristics are the most influential factors towards the adoption of Halal cosmetics.